(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The following ethnographic study was carried out in a public HEI located in southeast Mexico. The aim of the study was to verify the assumption that students enrolled in a second language course can change their monocultural mindset into an intercultural one. For this ethnographic study, four groups of 35 students each, belonging to four different knowledge areas: administration, accounting, economics, and marketing, were observed with a moderated level of observation. The categories obtained were problem-solving, dress code, personal space, accent, and colloquialism. The findings reveal that Marketing students are more prone than their peers to make a mindset change due to specific aspects of their career: if they want to sell products or services in another culture, they have to think of the host culture in order for products or services to be accepted. The internationalized curriculum is a suggested strategy in order to become a host university.